Kesehatan Mental Pada Remaja di Era Gempuran Game Online - Lathifah Aisha Nurwanti; Lanny Regina Susanti; Oxana Julian Tohir; Putri; {Ariffinto Frasatya; Sri Lestari (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2023)
In this era of technological development, engineering ideas can originate from small beginnings and grow into companies that have a profound impact on millions of people. It is not surprising, then, that many companies utilize technology as a means and infrastructure to implement their products. Online games, often played in a casual context for entertainment purposes, have features that constantly evolve alongside the virtual world. Consequently, online gaming has become a prominent aspect of teenagers' lifestyles, making it important to consider its potential effects on their mental health. Simultaneously, young people face increasing demands in academic and social domains. Adverse mental health in adolescents can significantly impact all aspects of their lives, including academics, social interactions, and physical well-being. Such mental health issues can have long-term consequences, such as depression, anxiety, eating disorders, and behavioral disorders.